The Paradigm Is Shifted to The Green: From Industrial to Ecological Convention - Irina ASEEVA; Sergey M. PYASTOLOV (Communications of International Proceedings, 2021)
The paper argues that the key feature in the actual context of management at various levels is the global phenomenon of transition. It is described in such terms as energy transition, green transition, technological transformations, creation of a new economic order. The authors propose that it is finally about mode of thinking and human nature in the long run. But organizations and communities are to perform needed changes in a short time. Thus, methods of institutional analysis of conventions, helical institutional development (HID) concept and other methodical instruments might be useful. The French convention model is enhanced with a set of propositions (discrete energy–information levels, HID requirements, etc.).
Keywords: Scientific and technological development; technological orders; technogenic civilization; International Economic Order; energy transitions; conflict of conventions; Helical Institutional Development; values.